Peran Guru dalam Meningkatkan Kemampuan Baca Tulis Al- Qur’an Santri Usia Dini di TPQ Madinatul Atfal Petanahan - Nada, Naeli Qotrin; Murtopo, Bahrun Ali (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
Al-Qur'an occupies an important position as the basis and source of Islamic education. For a Muslim, who is obedient to his God, maintaining and practicing the values ​​in the Qur'an is an obligation. The success or failure of the learning process of the Qur'an in these educational institutions depends on the quality and role of a teacher in the classroom. This study aims to find out what is the role of the TPQ teacher in improving the ability to read and write the Koran for young students at TPQ Madinatul Athfal Petanahan Kebumen. This research is a type of case study research, in which the authors collect data by conducting in-depth studies in the form of interviews with the Head of TPQ, TPQ Teachers and several TPQ Madinatul Atfal Petanahan Kebumen students as key informants (providers of key information at TPQ) as well as observing phenomena that occur and documenting those data. Then the data was analyzed using a qualitative descriptive method. The collected data were analyzed using data reduction, data presentation, and data verification. The results of this study concluded that the role of the teacher in an effort to improve the ability to read and write the Koran for young students at TPQ Madinatul Atfal Petanahan Kebumen is very good where there are several roles taken such as acting as a teacher, class manager, motivator, evaluator and demonstrator. Some of these roles are carried out by collaborating with teachers in other fields of study in improving the reading and writing ability of the Qur'an for early-age students